Resorbable membrane design: In vitro characterization of silver doped-hydroxyapatite-reinforced XG/PEI semi-IPN composite. (June 2023) - Dogan, Deniz; Erdem, Umit; Bozer, Busra M.; Turkoz, Mustafa B.; Yıldırım, Gurcan; Metin, Aysegul U.
Abstract: In this study, the production and characterization of silver-doped hydroxyapatite (AgHA) reinforced Xanthan gum (XG) and Polyethyleneimine (PEI) reinforced semi-interpenetrating polymer network (IPN) biocomposite, known to be used as bone cover material for therapeutic purposes in bone tissue, were performed. XG/PEI IPN films containing 2AgHA nanoparticles were produced by simultaneous condensation and ionic gelation. Characteristics of 2AgHA-XG/PEI nanocomposite film were evaluated by structural, morphological (SEM, XRD, FT-IR, TGA, TM, and Raman) and biological activity analysis (degradation, MTT, genotoxicity, and antimicrobial activity) techniques. In the physicochemical characterization, it was determined that 2AgHA nanoparticles were homogeneously dispersed in the XG/PEI-IPN membrane at high concentration and the thermal and mechanical stability of the formed film were high. The nanocomposites showed high antibacterial activity against Acinetobacter Baumannii (A.Baumannii), Staphylococcus aureus (S.aureus), and Streptococcus mutans (S.mutans). L929 exhibited good biocompatibility for fibroblast cells and was determined to support the formation of MCC cells. It was shown that a resorbable 2AgHA-XG/PEI composite material was obtained with a high degradation rate and 64% loss of mass at the end of the 7th day. Physico-chemically developed biocompatible and biodegradable XG-2AgHA/PEI nanocomposite semi-IPN films possessed an important potential for the treatment of defects in bone tissue as an easily applicable bone cover. Besides, it was noted that 2AgHA-XG/PEI biocomposite could increase cell viability, especially in dental-bone treatments for coating, filling, and occlusion. Graphical abstract: Image 1